ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN MANADO - Mongula, Eric C.; Massie, James D. D.; Worang, Frederik G. (Universitas Sam Ratulangi, 2021)
Since the 1998 economic crisis to the global financial crisis, Small and Medium Enterprises (SMEs) have been able to survive. Small and Medium Enterprises (SMEs) have an important role in supporting economic growth to date. This study aims to determine the analysis of the factors that influence the performance of small and medium enterprises in Manado. This research was conducted using a causal study with a quantitative approach in which data were obtained through interviews and questionnaires distributed to 100 respondents who were distributed to SMEs owners/managers in the city of Manado. This study has 20 variables. The sampling technique uses the purposive sampling method. The analysis technique used is the validity test, reliability test, factor analysis test, and multiple linear regression test. The test was carried out using the help of the SPSS program. The results showed that there were 3 factors that determine the performance of SMEs: (1) External Factors, (2) Planning and Relationship of Human Resources, (3) entrepreneurial skills and innovation.Keywords: factors influencing performance, small entreprises, medium enterprises